Co-benefits and trade-offs in the water–energy nexus of irrigation modernization in China. (3rd May 2016) - Cremades, Roger; G S A Rothausen, Sabrina; Conway, Declan; Zou, Xiaoxia; Wang, Jinxia; Li, Yu'e
Abstract: There are strong interdependencies between water use in agriculture and energy consumption as water saving technologies can require increased pumping and pressurizing. The Chinese Government includes water efficiency improvement and carbon intensity reduction targets in the 12th Five-Year Plan (5YP. 2011–2015), yet the links between energy use and irrigation modernization are not always addressed in policy targets. Here we build an original model of the energy embedded in water pumping for irrigated agriculture and its related processes. The model is based on the physical processes of irrigation schemes and the implication of technological developments, comprising all processes from extraction and conveyance of water to its application in the field. The model uses data from government sources to assess policy targets for deployment of irrigation technologies, which aim to reduce water application and contribute to adaptation of Chinese agriculture to climate change. The consequences of policy targets involve co-beneficial outcomes that achieve water and energy savings, or trade-offs in which reduced water application leads to increasing greenhouse gas (GHG) emissions. We analyze irrigation efficiency and energy use in four significant provinces and nationally, using scenarios based on the targets of the 12th 5YP. At the national scale, we find that expansion of sprinklers and micro-irrigation as outlined in the 5YP would increase GHG emissions from agricultural water use, however, emissions decrease in those provinces with predominant groundwater use and planned expansion of low-pressure pipes. We show that the most costly technologies relate to trade-offs, while co-benefits are generally achieved with less expensive technologies. The investment cost per area of irrigation technology expansion does not greatly affect the outcome in terms of water, but in terms of energy the most expensive technologies are more energy-intensive and produce more emissions. The results show that water supply configuration (proportion of surface to groundwater) largely determines the potential energy savings from reductions in water application. The paper examines the importance of fertigation and highlights briefly some policy implications.